Pembentukan Karakter Generasi Muda Berwawasan Nilai-Nilai Pancasila Melalui Video Game Bertema RPG - Arya Kresna (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2013)
This paper discusses the possibility to in still the values of the nation-state’s philosophy (Pancasila) on the young generation by using video games. Video games can facilitate the internalization of the values such as divinity, humanity, unity, democracy and justice more creatively and effectively as nowadays, young people are more interested in the video games that are played on computer, laptop and smart phones. The internalization of these values can be done explicitly and implicitly in every aspect of video game, through the plots of the game, the actor, dialogue and the content of the story of the game. The values of Pancasila will be analyzed hermeneutically to be improved in the electronic games. Then, we will discuss the narration and characters that will be analyzed philosophically to find capabilities of character of the values of Pancasila building. RPG video games can be used to build the characters of divinity, humanity, unity, democracy and just if these values can be expressed comprehensively in all aspects of video game RPG narration and characters